Moving Average as an Alternative Technique in Determination of Nuclear Shell Correction - Rizal Kurniadi; Yuda Satya Perkasa; Abdul Waris (Indonesian Journal of Physics, 2010)
Since Strutinsky has proposed shell correction for calculating nuclear mass at 1967, there are many studies concerning this topic. These former researches used the expansion of a Dirac delta function which uses hermite polynomials as a method. This paper discusses about an alternative technique to calculate shell correction by employing a moving average method. The results show that, although the proposed method can produce the shell correction, it still has enough discrepancies compared to the experimental nuclear mass.